The Role of the West Kutai Regional Government in Resolving Indigenous Land Conflict Between the Communities of Muara Tae and Muara Ponaq Villages - Heri supriyanto; Muh Fichriyadi Hastira; Alberto Noviano Patty; Sry Reski Mulka (Golden Ratio of Law and Social Policy Review, 2026)
Customary land conflicts are one of the structural problems that continue to arise in agrarian resource management in Indonesia, especially in areas with high intensity of resource extraction-based development. In the context of decentralization, local governments have significant administrative authority in determining territorial boundaries and managing social conflicts. This study aims to critically analyze the role of the West Kutai Regency Government in resolving the customary land conflict between Muara Tae Village and Muara Ponaq Village, which is centered on the Utaq Melinau customary forest area. The study uses a qualitative approach with a case study design. Data was obtained through in-depth interviews, field observations, and policy document analysis. Data analysis used Miles and Huberman's interactive model, with Ralf Dahrendorf's conflict and authority theoretical framework and Fisher and Ury's conflict resolution theory. The results show that the local government procedurally positioned itself as a neutral mediator through dialogue facilities and administrative mechanisms. However, structurally, the government remains an authoritative actor that shapes the arena of conflict through policies on the determination of administrative boundaries. The neutrality of the local government is administrative in nature, but does not fully reflect substantive justice because administrative decisions have a direct impact on the legitimacy of customary land claims and the distribution of access to resources. This conflict also has an impact on ecological degradation and changes in the economic structure of indigenous communities.The theoretical contribution of this research lies in the development of the concepts of procedural neutrality and structural neutrality in local agrarian conflicts. Practically, this research emphasizes the need to reformulate the of territorial boundary policies based on the recognition of customary rights, participatory verification, and community-based ecological protection.